PENGEMBANGAN SIMULATOR PENGAJARAN KONSEP MATEMATIKA BERBANTUAN GEOMETER’S SKETCHPAD - Nugraha, Depi Ardian; Santika, Satya; Hermanto, Redi (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2024)
This study aims to develop a math concept learning simulator with the help of a sketchpad geometer, so that the products resulting from this research can be utilized by teachers and students. Products developed using the ADDIE model development method and data collection techniques through filling out questionnaires and sheet validation. Sources of data that have been taken in this study are teacher responses, student responses, assessments from material experts and the media on the quality of the teaching simulator for teaching mathematical concepts with the help of the resulting sketchpad geometer. Based on the results of data collection and analysis that has been carried out, the results obtained are 1) development of a simulator media for learning mathematical concepts assisted by a sketchpad geometer using the ADDIE method (analysis, design, development, implementation and evaluation), 2) a media simulator for learning mathematical concepts assisted by a sketchpad geometer is very feasible for use in the mathematics learning process, 3) the teacher's response to the use of the simulator media for teaching mathematical concepts assisted by positive geometric sketches, 4) the interest of students in the learning process using the simulator media for learning mathematical concepts assisted by geometric sketches is very high.